Splitting in schizophrenia and borderline personality disorder - Pec, Ondrej; Bob, Petr; Raboch, Jiri (PLoS One, 2014)
BACKGROUND: Splitting describes fragmentation of conscious experience that may occur in various psychiatric disorders. A purpose of this study is to examine relationships between psychological process of splitting and disturbed cognitive and affective functions in schizophrenia and borderline personality disorder (BPD). METHODS: In the clinical study, we have assessed 30 patients with schizophrenia and 35 patients with BPD. The symptoms of splitting were measured using self-reported Splitting Index (SI). As a measure of semantic memory disorganization we have used verbal fluency test. Other psychopathological symptoms were assessed using Health of the Nation Outcome Scale (HoNOS). RESULTS: Main results show that SI is significantly higher in BPD group than in schizophrenia, and on the other hand, verbal fluency is significantly lower in schizophrenia group. Psychopathological symptoms measured by HoNOS are significantly higher in the BPD group than in schizophrenia. Significant relationship was found between verbal fluency and the SI "factor of others" (Spearman r = -0.52, p<0.01) in schizophrenia patients. CONCLUSIONS: Processes of splitting are different in schizophrenia and BPD. In BPD patients splitting results to mental instability, whereas in schizophrenia the mental fragmentation leads to splitting of associations observed as lower scores of verbal fluency, which in principle is in agreement with Bleuler's historical concept of splitting in schizophrenia.
Keywords: Schizophrenic Psychology; dospělí; hraniční porucha osobnosti; neparametrická statistika; neuropsychologické testy; Statistics, Nonparametric; lidé; Female; mužské pohlaví; Male; Borderline Personality Disorder; Neuropsychological Tests; schizofrenie (psychologie); Adult; ženské pohlaví; Humans